The use of a written assessment checklist for the provision of emergency contraception via community pharmacies: a simulated patient study - Schneider CR; Gudka S; Fleischer L; Clifford RM (Centro de Investigaciones y Publicaciones Farmaceuticas, 2013)
Background: The Pharmaceutical Society of Australia recommends use of a written assessment checklist prior to supply of emergency contraception by pharmacists. Objective: The aim of this research was to determine the prevalence of use of a written assessment checklist by community pharmacists and secondly, to ascertain the effect of the checklist on appropriate assessment and supply.Methods: Three female simulated patients visited 100 randomly selected pharmacies requesting supply of 'the morning after pill'. Information provided when assessed by the pharmacist was that she had missed one inactive pill of her regular hormonal contraception. The amount of assessment provided and the appropriateness of supply were used as comparative outcome measures.Results: Eighty-three pharmacies used a written assessment checklist. Twenty-four of the pharmacies visited provided the appropriate outcome of non-supply. Pharmacies that used a written assessment checklist provided a greater quantity and consistency of assessment (11.3 ±2.5 v. 6.5 ±3.8 questions, p<0.0001) but this did not result in an improved frequency of an appropriate outcome (20%, n=16 v. 23%, n=3). Conclusions: While a written patient assessment checklist improved the quantity and consistency of patient assessment, it did not improve the advice provided by community pharmacies when handling requests for emergency contraception.